Tahapan Pengambilan Keputusan Menjadi Pendeta - ., Sevianti; Putra, Denny (Noetic Psychology, 2014)
AbstractÃÂ Decision to become a pastor at a young age while having a career is not an easy thing to do because one of the developmental tasks of young adults is pursuing a higher position in his or her career. Career as a pastor tends to be underestimated compared to that of career in other fields. The reason is because pastorÃ¢â¬â¢s salary is considerably less than that of the other career, not to mention the uncertainty in receiving it on regular basis. It will depend on the contribution from church congregation or church policy. Individuals who decide a career to be a pastor means that he or she is ready to accept the roles and tasks involved. In addition, a pastor is considered a Ã¢â¬Åspecial callingÃ¢â¬Â from GodÃÂ so it must be accepted with gratitude. In this study the authors would like to see the stages of individual decision-making as a young adult to accept his calling to be a pastor. This study uses qualitative methods, with in-depth interviews and observation. Subjects in this study were three individuals who had been called to be pastors as a young adulthood while he still hold a job or career. This study obtained a clear picture of the decision-making stages by Jennis & Mann (1977), and found three factors that influence decision-making, which are circumstance, mood, and belief. Keywords: Young Adults, Decision Making Stages, PastorÃÂ